Nilai Moral dan Nilai Budaya dalam Cerita Rakyat Kutai “Asal Usul Danau Lipan” Kecamatan Muara Kaman - Fatimah Zahro; Syaiful Arifin (YASIN, 2026)
Each region has cultural heritage that serves as a distinctive characteristic and identity of its community. However, the values contained in folktales, particularly legends, have begun to shift along with the development of the times. This study aims to describe the moral values and cultural values contained in the folktale The Origin of Lake Lipan. This study used a qualitative approach, with library research and note-taking techniques as data collection methods. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that the moral values in the folktale The Origin of Lake Lipan included the relationship between humans and God, namely praying; the relationship between humans and themselves, namely perseverance, courage, and maintaining self-respect; and the relationship between humans and others, namely maintaining etiquette and entertaining guests. In addition, the cultural values found included religious systems, social systems, language, arts, livelihoods, and systems of living equipment. The conclusion of this study emphasizes that the folktale The Origin of Lake Lipan contains important moral and cultural values as a means of transmitting character, cultural identity, and local wisdom. The implications of this study indicate the need to preserve folktales as a source of value learning and regional cultural strengthening amid social change.